Isolated Brain Stem Lesion in Children: Is It Acute Disseminated Encephalomyelitis or Not? - Alper, G.; Sreedher, G.; Zuccoli, G. (American Journal of Neuroradiology, 2013)
SUMMARY: Isolated brain stem lesions presenting with acute neurologic findings create a major diagnostic dilemma in children. Although the brain stem is frequently involved in ADEM, solitary brain stem lesions are unusual. We performed a retrospective review in 6 children who presented with an inflammatory lesion confined to the brain stem. Two children were diagnosed with connective tissue disorder, CNS lupus, and localized scleroderma. The etiology could not be determined in 1, and clinical features suggested monophasic demyelination in 3. In these 3 children, initial lesions demonstrated vasogenic edema; all showed dramatic response to high-dose corticosteroids and made a full clinical recovery. Follow-up MRI showed complete resolution of lesions, and none had relapses at >2 years of follow-up. In retrospect, these cases are best regarded as a localized form of ADEM. We conclude that though ADEM is typically a disseminated disease with multifocal lesions, it rarely presents with monofocal demyelination confined to the brain stem. ADEMacute disseminated encephalomyelitisCISclinically isolated syndromeCPMcentral pontine myelinolysisIPMSSGInternational Pediatric Multiple Sclerosis Study GroupPOLGpolymerase subunit-gamma